1155 Mini break intervention in preventing asthenopia among drawing workers using standard and widescreen size vdt at construction company in jakarta. (24th April 2018) - Hidayat, B; Rahayu, T; Kekalih, A
Abstract : Introduction: Astenopia has the effect of decreasing work productivity and health condition. Although the computer has not been proven to make permanent damage to the eyes but temporary discomfort due to tired eyes can reduce productivity. The impact is on lost working hours and reduced job satisfaction. In indonesia, In a diagnostic test of tired eye screening tool for office workers in north Jakarta, astenopia prevalence was found at 80%. Asthenopia among drawing workers is becoming my attention because there are significant number of drawing workers as office workers in Jakarta, Indonesia and limited data regarding their health effect from their work Methods: This is an experimental study with cross over design. The number of subjects who participated in this study were 66 participants. Intervention of no mini break and mini break were given to workers who used VDT size 4:3 and VDT size 16:9. Data was revealed from the difference of NPC before and after 4 hours of VDT exposure and 4 hours of exposure with a 15 min mini break after 2 hours of work to both groups (sub group of VDT 4:3 and VDT 16:9) using RAF (Royal Air Force) ruler. Results: The users of VDT size 4:3 have difference of NPC 2, 89±1, 11 cm in no mini break intervention and 1, 42±1, 01 cm in mini break intervention. The users of VDT size 16:9 have difference NPC 3, 02±1, 04 cm in no mini break intervention and 1, 41±1, 10 cm in mini break intervention. The difference of convergence power between no mini break and mini break intervention for VDT size 4:3 (p=0.000) and size 16:9 users (p=0.000) was statistically significant. There was no significant difference statistically in convergence power in no mini break intervention between VDT size 4:3 and size 16:19 users (p=0, 6251) and neither in mini break intervention between VDT size 4:3 and size 16:9 users (p=0, 9694). Conclusion: The convergence power is different significantly between working without mini break and with mini break in both of VDT users size 4:3 and 16:9. There is no diference significantly between VDT users size 4:3 and 16:9 in no mini break intervention as well as mini break intervention. This is probably because the measurement is only based on NPC and experimental limitations. It takes other parameters to measure asthenopia due to VDT usage as asthenopia is a sign of computer vision syndrome .